Faktor-Faktor yang Mempengaruhi Online Self-Disclosure pada Remaja: Kajian Literatur Sistematis - Aditya Karna, Manik; Ediati, Annastasia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Online self-disclosure activities have several differences compared to direct or face-toface self-disclosure, adolescents reveal very intimate information, this will be more likely to be interpreted as inappropriate when done in public rather than private. This study aims to provide an overview of the factors that cause self-disclosure in adolescents. The method used in this research is a systematic literature review using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Searching for articles in this study used several databases namely Google Scholar, ResearchGate, Elsevier, Emerald, and ScienceDirect. Inclusion criteria 1) research articles from 2019-2023; 2) journal articles published in journals and fully written in Indonesian and English; 3) using quantitative and qualitative research designs; 4) research that focuses on self-disclosure online in adolescents. The results of the study show that the factors that influence self-disclosure online are self-esteem, loneliness, personality, social anxiety, and negative emotions. In addition, there are also moderating factors namely value, and online disinhibition.